Mass Loss of Platinum-Rhodium Thermocouple Wires at 1324°C : Lower mass loss observed with enclosed wires. Issue 4 (1st October 2021) - Uthayakumaar, Sivahami; Davidson, Stuart; Pearce, Jonathan
It is known that platinum-rhodium thermocouples exhibit mass loss when in the presence of oxygen at high temperatures due to the formation of volatile oxides of platinum and rhodium. The mass losses of platinum, Pt-6%Rh and Pt-30%Rh wires, commonly used for thermocouples, were considered in this paper to characterise the mass loss of wires of the three compositions due to formation and evaporation of the oxides PtO2 and RhO2 under the conditions that would be seen by thermocouples used at high temperature. For the tests, the wires were placed in thin alumina tubes to emulate the thermocouple format, and the measurements were performed in air at a temperature of 1324°C, i.e. with oxygen partial pressure of 21.3 kPa. It was found that the mass loss of the three wires increases linearly with elapsed time, consistent with other investigations, up to an elapsed time of about 150 h, but after that, a marked acceleration of the mass loss is observed. Remarkably, previous high precision studies have shown that a crossover after about 150 h at 1324°C is also observed in the thermoelectric drift of a wide range of platinum-rhodium thermocouples, and the current results are compared with those studies. The mass loss was greatest for Pt-30%Rh, followed by Pt6%Rh, then platinum.